Optimal dynamic matching - Mariagiovanna Baccara; SangMok Lee; Leeat Yariv (Theoretical Economics, 2020)
We study a dynamic matching environment where individuals arrive sequentially. There is a tradeoff between waiting for a thicker market, allowing for higher-quality matches, and minimizing agents' waiting costs. The optimal mechanism cumulates a stock of incongruent pairs up to a threshold and matches all others in an assortative fashion instantaneously. In discretionary settings, a similar protocol ensues in equilibrium, but expected queues are inefficiently long. We quantify the welfare gain from centralization, which can be substantial, even for low waiting costs. We also evaluate welfare improvements generated by alternative priority protocols.
Keywords: D47; 330; Dynamic matching; mechanism design; organ donation; market design